Improving maternal knowledge and children's eating pattern by a combination of a booklet and food journaling - Andin Sefrina; Norif Didik Nur Imanah (Journal of Holistic Nursing Science, 2023)
Health education is a promising intervention to improve the mother's nutrition knowledge. However, a study focusing on using booklets and food journaling is limited in the literature. This study aims to assess the effectiveness of health education using a booklet and food journaling on the daily nutrition pattern of children. The study design is a pre-experiment pretest-posttest single group design using 19 participants who met the criteria. The participants received intervention one session of health education using a booklet and 14 days of food journaling activity for the children eating patterns. Data analysis used univariate analysis, and Wilcoxon signed rank. The study showed significant differences in maternal knowledge before and after intervention (p<0.05). However, there are no significant differences in children eating patterns (p>0.05). The findings suggest that health education using a booklet and food journaling book effectively increases maternal knowledge but does not change children's eating patterns. Keywords: Health education; food journaling; booklet; eating pattern in children; nutritional status